2017
DOI: 10.3389/fimmu.2017.00271
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes in Inflammation-Induced Cancer

Abstract: The inflammasome is an important multiprotein complex that functions during inflammatory immune responses. The activation of inflammasome will lead to the autoactivation of caspase-1 and subsequent cleavage of proIL-1β and proIL-18, which are key sources of inflammatory manifestations. Recently, the roles of inflammasomes in cancers have been extensively explored, especially in inflammation-induced cancers. In different and specific contexts, inflammasomes exhibit distinct and even contrasting effects in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 235 publications
(324 reference statements)
0
66
0
Order By: Relevance
“…NLRP1 (NALP1) is the component of the first identified inflammasome [28]. It is a pattern recognition receptor activated by various bacterial toxins including Bacillus anthracis lethal toxin [29]. For our analysis of gene expression, we also selected PKR kinase (coded by the EIF2AK2 gene), because it has antiviral effector functions and can participate in the activation of p53 by phosphorylating Ser392 [30].…”
Section: Treatment With a + N Or Cpt Upregulates Proteins Associated mentioning
confidence: 99%
“…NLRP1 (NALP1) is the component of the first identified inflammasome [28]. It is a pattern recognition receptor activated by various bacterial toxins including Bacillus anthracis lethal toxin [29]. For our analysis of gene expression, we also selected PKR kinase (coded by the EIF2AK2 gene), because it has antiviral effector functions and can participate in the activation of p53 by phosphorylating Ser392 [30].…”
Section: Treatment With a + N Or Cpt Upregulates Proteins Associated mentioning
confidence: 99%
“…Moreover, tumor cells can escape immune surveillance cells [4], promoting immune tolerance to the tumor by favoring the establishment of a Th2 immune response, expressing cytokines like IL-4, IL-10, and TGF-β [5]. Previous studies show that a sustained immune change from Th2 to Th1 profiles is critical for tumor cell death [6].…”
Section: Introductionmentioning
confidence: 99%
“…The various inflammasomes and inflammatory cytokines and chemokines play contrasting roles in lung, breast, gastric, liver, colon, and prostate cancers and in glioblastomas [44]. Recently, it was reported that Inflammasomes may also exert anticancer effects by specialized programmed cell death called pyroptosis and immune regulatory functions [45]. Our previous work showed that the inflammasome activity was increased in ASH specimens [46].…”
Section: Discussionmentioning
confidence: 99%